A meta-analysis of emotional disorders as possible risk factors for chronic periodontitis - Liu, Fei (Medicine (Baltimore), 2018)
The aim of the present meta-analysis was to evaluate scientific evidence on the association between emotional disorder (depression and anxiety) and chronic periodontitis. An overall electronic literature search in PubMed, ISI Web of Science, Cochrane Library, and China National Knowledge Infrastructure was undertaken up to November 2017. Newcastle–Ottawa scale was applied to ascertain the validity of each eligible study. Stata statistical software was used to perform meta-analysis. The strength of the association between periodontitis and emotional disorder was measured by odds ratios (ORs) with their 95% confidence intervals (95% CIs). Subgroup analysis and sensitivity analysis were performed. Publication bias was assessed through funnel plots and Begger's test. A total of 14 eligible articles were included in the meta-analysis, 6 of them were focused exclusively on depression, whereas 8 studies investigated both depression and anxiety. There was significant association between emotional disorder and chronic periodontitis (OR = 1.54, 95% CI = 1.27–1.86). Sensitivity analyses confirmed the stability of the present results. No evidence of asymmetry was observed in Begger's test. This meta-analysis demonstrates significant association between emotional disorder (including anxiety and depression) and chronic periodontitis. Nevertheless, the result should be interpreted with caution because of the potential bias and confounding in the included studies.